Current problems of ecology, agriculture and animal welfare in the context of global climate changes : afterword - Kalinichenko, Alena; Kalinichenko, Olena; Kalinichenko, O. O.; Kalinichenko, Olena O.; Kalinichenko, O.; Kalynychenko, O.; Калиниченко, Олена Олександрівна; Kobec, A. S.; Kobets, A. S.; Kobets, A.; Kobets, Anatoly Stepanovich; Kobets, Anatoly S.; et al. (Dnipro State Agrarian and Economic University, 2020)
The material for the analysis were messages (abstracts) on the main areas of the 1st International Scientific and Practical Conference on «Animal Welfare in the Conditions of Global Climate Changes» (Dnipro, April 21-22, 2020) (AWCGCC), which made it possible to summarize current issues in the field of ecology, agriculture and animal welfare in the context of global climate changes. Проведено аналіз доповідей І Міжнародної науково-практичної конференції «Добробут тварин в умовах глобальних змін клімату» (Дніпро, 21-22 квітня 2020 р.) (AWCGCC), який дозволив узагальнити актуальні проблеми в сфері екології, сільського господарства і добробуту тварин в контексті глобальних кліматичних змін.
Актуальні питання екології, сільського господарства та добробуту тварин в контексті глобальних кліматичних змін : замість післямови
Калиниченко Олена Олександрівна https://orcid.org/0000-0002-5391-0281 Піщан Станіслав Григорович https://orcid.org/0000-0001-8579-9429 Похил Олена Миколаївна https://orcid.org/0000-0002-7477-6501 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: adaptive strategies; адаптивні стратегії; ecological problems; екологічні проблеми; monitoring; моніторинг; climate changes; кліматичні зміни; animal welfare; добробут тварин